Budget Processes and Commitment to Fiscal Discipline. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper develops a political-economy model of the budget process focusing on the common pool problem of the public budget. We show that the externality arising from the fact that public spending tends to be targeted at individual groups in society while the tax burden is widely dispersed creates a bias towards excessive expenditures and debt. This bias can be reduced by introducing elements of centralization in the budget process, that is, institutional structures that strengthen a comprehensive view of the budget over the particularistic view of the spending ministers and the members of parliament. Using examples from EC countries, we show how budget processes lack or possess such elements. We then present empirical evidence supporting the claim that centralizing elements reduce the deficit bias. The last section concludes with models for reform of the budget process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet